The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/0034-737x201764010012
|View full text |Cite
|
Sign up to set email alerts
|

Produção de cultivares de alface americana sob dois sistemas de cultivo

Abstract: Produção de cultivares de alface americana sob dois sistemas de cultivoA alface é cultivada em todas as regiões brasileiras, porém há restrições ao seu cultivo em virtude de sua sensibilidade às condições adversas de temperatura, umidade do ar e disponibilidade de água. Diante disso, objetivou-se, com este experimento, avaliar a produção de quatro cultivares de alface americana, sob dois sistemas de cultivo. O delineamento experimental utilizado foi o de blocos ao acaso, em esquema de parcelas subdivididas. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1
14

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 13 publications
3
11
1
14
Order By: Relevance
“…Concerning stem length, our results were superior to those reported by Brzezinski et al (2017). The authors found an average value of 2.54 cm for stem diameter when studying the production of lettuce from Angelina, Rubette, Great Lakes 659 and Tainá varieties in open field.…”
Section: Resultscontrasting
confidence: 89%
“…Concerning stem length, our results were superior to those reported by Brzezinski et al (2017). The authors found an average value of 2.54 cm for stem diameter when studying the production of lettuce from Angelina, Rubette, Great Lakes 659 and Tainá varieties in open field.…”
Section: Resultscontrasting
confidence: 89%
“…Lettuce (Lactuca sativa L.) is the most important leafy green vegetable in Brazil and in the world (Brzezinski et al, 2017;Yuri et al, 2017). According to Queiroz, Cruvinel and Figueiredo (2017), the current lettuce crop area in Brazil occupies approximately 35,000 hectares, and approximately 60% of the national market is occupied by cultivars that have curly lettuce leaves (Valeriano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Brzezinski et al (2017) destacam que, além das características do sistema de produção, a altura das plantas da cultura da alface também pode variar de acordo com as características genéticas distintas de cada cultivar, em relação ao tamanho médio de plantas.…”
Section: Tratamentosunclassified